2017
DOI: 10.2147/cia.s147585
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative delirium after hemiarthroplasty in elderly patients aged over 70 years with displaced femoral neck fracture

Abstract: PurposePostoperative delirium is a risk factor for worse outcome after hip fracture surgery in elderly patients. Postoperative delirium is associated with anesthesia, postoperative pain, and patient factors. We investigated the incidence, predictors, and prognostic implications of post-operative delirium after hemiarthroplasty (HA) in elderly patients with femoral neck fracture.Patients and methodsA total of 356 consecutive patients aged >70 years who underwent HA for femoral neck fracture were enrolled. Diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 19 publications
2
40
0
1
Order By: Relevance
“…The incidence of delirium in our dataset is similar to results obtained from other studies concentrating on cardiac surgery; however, it is still lower than in the general ICU setting 2 , 9 , 10 , 20 , 21 or after other types of major surgery. 22 This may be related to factors not measured such as postoperative ICU design, patient preparation prior to surgery, or population differences in different geographical settings around the world. To our knowledge this is the first analysis reporting data specifically on elderly and very elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of delirium in our dataset is similar to results obtained from other studies concentrating on cardiac surgery; however, it is still lower than in the general ICU setting 2 , 9 , 10 , 20 , 21 or after other types of major surgery. 22 This may be related to factors not measured such as postoperative ICU design, patient preparation prior to surgery, or population differences in different geographical settings around the world. To our knowledge this is the first analysis reporting data specifically on elderly and very elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have made various attempts to investigate the incidence and risk factors for postoperative delirium after hip fracture surgeries [11][12][13][14], or incident hip fracture after the stroke [8,9,15]. However, there is still a lack of epidemiologic data on postoperative stroke following surgery of hip fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-two studies reported delirium (5 RCTs, 35-39 9 prospective 18 40-47 and 8 retrospective studies [48][49][50][51][52][53][54][55] ); 58 studies reported mortality (2 RCTs, 35 38 12 prospective 42 45 96 109 110 ); 11 studies reported functional outcome (3 RCTs, 35 36 111 4 prospective 42 45 103 112 and 4 retrospective studies 62 73 105 113 ); 5 studies reported discharge location (2 prospective 43 114 and 3 retrospective studies 21 48 99 ).…”
Section: Resultsmentioning
confidence: 99%